Seascapes Learn to paint step to step - Germain, Frank (California Walter Foster Publishing, 2010)
painting realistic sand-using special techniques - rendering waves -changing mood with color
Arts(Drawing)
1 6 13
Keywords: Drawing; Watercolor painting -- Technique; (3GdQSes